Analisis Return Metode Dogs Of The Dow dengan Uji-T Pada IDXHIDIV20 - Helynda Mulya Arga Retha; Retno Budiarti (Politeknik Caltex Riau, 2022)
All investors should strive to beat the market, that is, get a higher return than the market return, which is usually represented by an index. Composite Stock Price Index is the name of the stock market index in Indonesia (IHSG). The